Bogong Moths Are Well Camouflaged by Effectively Decolourized Wing Scales - Stavenga, Doekele G.; Wallace, Jesse R. A.; Warrant, Eric J. (Frontiers in Physiology, 2020)
Moth wings are densely covered by wing scales that are assumed to specifically function to camouflage nocturnally active species during day time. Generally, moth wing scales are built according to the basic lepidopteran Bauplan, where the upper lamina consists of an array of parallel ridges and the lower lamina is a thin plane. The lower lamina hence acts as a thin film reflector having distinct reflectance spectra that can make the owner colourful and thus conspicuous for predators. Most moth species therefore load the scales’ upper lamina with variable amounts of melanin so that dull, brownish colour patterns result. We investigated whether scale pigmentation in this manner indeed provides moths with camouflage by comparing the reflectance spectra of the wings and scales of the Australian Bogong moth (Agrotis infusa) with those of objects in their natural environment. The similarity of the spectra underscores the effective camouflaging strategies of this moth species.